2018
DOI: 10.1111/ene.13792
|View full text |Cite
|
Sign up to set email alerts
|

The neurologist's approach to cerebral infarct and transient ischaemic attack in patients receiving anticoagulant treatment for non‐valvular atrial fibrillation: ANITAFA study

Abstract: Patients with AF treated with DOACs who experienced AIS more frequently had transient symptoms (transient ischaemic attack), less symptomatic hemorrhagic transformation and a shorter mean stay than those treated with VKAs. Most patients who had been previously anticoagulated with AIS received long-term treatment with DOACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
0
10
0
11
Order By: Relevance
“…Interestingly, a recent study suggested that CMBs are an independent predictor of HT following IV thrombolytic therapy in acute ischaemic stroke [4]. This thought is particularly important in this study [1], especially considering that CMBs have not been shown to predict HT in the absence of IV thrombolysis [4].…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Interestingly, a recent study suggested that CMBs are an independent predictor of HT following IV thrombolytic therapy in acute ischaemic stroke [4]. This thought is particularly important in this study [1], especially considering that CMBs have not been shown to predict HT in the absence of IV thrombolysis [4].…”
mentioning
confidence: 85%
“…Secondly, did HAS-BLED scores have any correlation with increased HT in either group [1]? The HAS-BLED score is used to assess the 1-year risk of major bleeding in patients with atrial fibrillation [5].…”
mentioning
confidence: 96%
See 3 more Smart Citations